PENGARUH EARNING VOLATILITY DAN LEVERAGE TERHADAP VOLATILITAS HARGA SAHAM SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sinta Adelia Lubis; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to test partially and simultaneously the effect of Earning Volatility and Leverage on Stock Price Volatility. Independent variables in this study are Earning Volatility and Leverage and dependent variable is Stock Price Volatility. This study uses secondary data in the form of company financial reports and annual reports on annual reports of property and real estate companies listed on the Stock Exchange. This study use purposive sampling technique, this which is used is 15 companies and the data analysis use simple linear regression analysis, multiple linear regression, T test, F test and coefficient of determination test using SPSS 16 devices. The results show that the variable volatility earnings partially (t test) influences the volatility of stock prices of property and real estate companies listed on the Indonesia Stock Exchange, the leverage variable partially (t test) influences the volatility of listed property and real estate on the Indonesia Stock Exchange. Simultaneous test results (f test) indicate the influence of variable volatility and leverage earnings on stock price volatility in property and real estate companies listed on the Indonesia Stock Exchange.  Keywords: Earning Volatility, Leverage, and Stock Price Volatility